2001
DOI: 10.1161/01.cir.103.12.1618
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate Restores Endothelium-Dependent Vasodilation Impaired by Acute Hyperglycemia in Humans

Abstract: Vitamin C administration restores endothelium-dependent vasodilation impaired by acute hyperglycemia in healthy humans in vivo. These findings suggest that hyperglycemia may contribute in part to impaired vascular function through production of superoxide anion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
194
6
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(218 citation statements)
references
References 46 publications
15
194
6
2
Order By: Relevance
“…Rather surprisingly, the results of these studies are not consistent [17,19] despite the fact that hyperinsulinaemia itself has been claimed to have a selective, major negative effect on this segment of the vascular tree [39,40]. The evidence in resistance vessels is scarce [22,41], comes from a single laboratory and describes an inhibitory effect that is small (ACh response reduced by 20%), only detectable for unphysiological degrees of hyperglycaemia (over 16 mmol/l) maintained for 6 h and effectively prevented by a very small gradient (35 pmol/l) of hyperinsulinaemia. Other laboratories have reached opposite conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…Rather surprisingly, the results of these studies are not consistent [17,19] despite the fact that hyperinsulinaemia itself has been claimed to have a selective, major negative effect on this segment of the vascular tree [39,40]. The evidence in resistance vessels is scarce [22,41], comes from a single laboratory and describes an inhibitory effect that is small (ACh response reduced by 20%), only detectable for unphysiological degrees of hyperglycaemia (over 16 mmol/l) maintained for 6 h and effectively prevented by a very small gradient (35 pmol/l) of hyperinsulinaemia. Other laboratories have reached opposite conclusions.…”
Section: Discussionmentioning
confidence: 90%
“…It has been reported that infusion with vitamin C leads to an increase in forearm blood flow of 1 . 4 ml/100 ml per min in subjects after a 6 h hyperglycaemic clamp (36) . Vitamin C supplementation has been shown to improve endothelium-dependent vasodilation, measured by flow-mediated dilation, from 4 .…”
Section: Carotenoids: Flavonoids: Cvd: Laser Doppler Imagingmentioning
confidence: 92%
“…While the vasodilating effects of insulin are established [9,10], the direct vascular actions of short-term hyperglycaemia are largely unknown. Studies investigating the effects of high glucose on macrovascular and microvascular perfusion have yielded conflicting results: some have shown attenuated vasodilation [11,12,13,14,15,16], some have demonstrated enhanced vasodilation [17,18,19,20], whereas others found no changes in vascular tone [21,22,23]. The present study was designed to gain deeper insights into the immediate effects of high glucose on endothelial NO formation and vascular tone, and its stimulatory role on the vascular effects of insulin.…”
Section: Introductionmentioning
confidence: 96%